N.C. Gerson papers - Gerson, N. C.
Correspondence, biographical material, drafts and offprints of scientific articles, memoranda, minutes, notes and equations, reports, research material, rosters, schematics, and other papers documenting Gerson's career as a research physicist and his service as a member of the U.S. National Committee for the International Geophysical Year (1957-1958). Organizations represented include the American Geophysical Union, Cosmos Club, Mitre Corporation, National Academy of Sciences, and Syracuse University Research Corporation. Topics include airglow and auroras, ballistics research, cosmic rays, expeditions to Antarctic and Arctic regions, geomagnetism, glaciology, gravity, ionospheric research, meteorology, oceanography, radio wave propagation, rocket exploration of the upper atmosphere, rockets and artificial satellites, scientific cooperation between the Soviet Union and the United States, seismology, and solar activity.
Research physicist. Full name: Nathaniel Charles Gerson. Born 1915; died 2002.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: American Geophysical Union; Cosmos Club (Washington, D.C.); Mitre Corporation; National Academy of Sciences (U.S.); Syracuse University. -- Research Corporation; United States. -- National Committee for the International Geophysical Year; Airglow; Artificial satellites in ionospheric research; Atmosphere, Upper -- Rocket observations; Auroras; Ballistics -- Research; Cosmic rays; Geomagnetism; Geophysics -- International cooperation; Glaciology; Gravity; International Geophysical Year (1957-1958); Meteorology; Oceanography; Radio wave propagation; Rockets (Aeronautics); Science -- International cooperation; Science -- Soviet Union; Science -- United States; Scientific expeditions -- Antarctica; Scientific expeditions -- Arctic regions; Seismology; Solar activity; Physicists